Late Antiquity Revisited: Angelika Neuwirth's View on the Story of Prophet Abraham - Zubaidi, Sujiat; Asnawi, Aqdi Rofiq; Kuswaya, Adang; Bandiyah, Siti Us; Ridwan, Muhammad K. (Journal of Al-Tamaddun, 2025)
This article sheds light on Angelika Neuwirth’s perspective on the Late Antiquity of Prophet Abraham in the Qur’an. Neuwirth examines the connections between the Qur’anic, Jewish, Christian, and pagan traditions, considering the development of religions and the collapse of the Roman civilisation in Europe during the Late Antiquity. She aims to foster dialogue between scriptures, highlighting the shared history of the Qur’an with other scriptures as part of the Abrahamic religion during that era. Using a critical study approach, this article analyses Neuwirth’s ideas and compares them with Islamic literature to critique her thoughts. The results indicate that Neuwirth employs literary and historical criticism through microstructure analysis and intertextual studies to interpret Quranic verses. She starts by distinguishing between the two manifestations of the Qur’an: oral transmission (Qur’ān) and written form (Kitāb). Neuwirth then deconstructs the revelation, treating the Qur’an as an invisible text to facilitate its literal and historical study. Her method resembles a hermeneutic development when studying Qur’anic verses and focuses on a diachronic reading between the Qur’an and the Bible.